STRATEGI SUPERVISI DALAM PENINGKATAN KUALITAS PEMBELAJARAN DAN MANAJEMEN KEUANGAN: STUDI LITERATUR - Savitri, Wici Aan; Hatta, Mega Amelia Prihatini; Koto, Rahmat Desman; Yuliana, Yuliana; Simatupang, Wakhinuddin; Wagino, Wagino (Ensiklopedia of Journal, 2025)
Abstract: Educational supervision plays an important role in improving the quality of learning and financial management in educational institutions. This study analyzes effective supervision strategies in these two main aspects through a literature study approach. The study results show that clinical, academic, and technology-based supervision approaches can improve the professionalism of educators and create a conducive learning environment. On the other hand, transparent and accountable financial management, such as through the School Revenue and Expenditure Budget Plan (RAPBS) and the analysis of the benefits of education costs, is a key element in supporting the operational sustainability of educational institutions. The study provides strategic recommendations to integrate innovative supervision approaches with efficient financial management to achieve higher education quality standards.Keywords: educational supervision, financial management, clinical supervision, educational technology, professional development.